A randomized trial comparing physostigmine vs lorazepam for treatment of antimuscarinic (anticholinergic) toxidrome. (3rd August 2021) - Wang, George Sam; Baker, Keith; Ng, Patrick; Janis, Gregory C.; Leonard, Jan; Mistry, Rakesh D.; Heard, Kennon
Abstract: Background: Toxicity from antimuscarinic agents precipitates a constellation of signs and symptoms; two of the most significant are agitation and delirium. Benzodiazepines are commonly used for treatment; physostigmine is also effective but is underutilized due to concerns for safety and short duration of action. The objective of this study was to compare lorazepam to physostigmine for the treatment of antimuscarinic delirium and agitation. Methods: This was a blinded, randomized clinical trial in patients presenting for antimuscarinic toxidrome. Inclusion criteria were: ≥10–<18 years old, at least one central and two peripheral antimuscarinic symptoms, delirium and moderate agitation. Subjects were randomized to either (1) lorazepam bolus (0.05 mg/kg) followed by a 4-h normal saline infusion, or (2) physostigmine 0.02 mg/kg bolus followed by a 4-h physostigmine infusion (0.02 mg/kg/h). Primary outcomes were the control of delirium and agitation after bolus and during the infusion. Results: Ten (53%) subjects were enrolled in the lorazepam arm, 9 (47%) in the physostigmine arm. Diphenhydramine was the most common agent ingested (16, 84%). Fewer patients receiving physostigmine had delirium after the initial bolus (44% vs 100%, p  = 0.01) and at the 4th hour of infusion (22% vs 100%, p  < 0.001) compared to patients who received lorazepam. There was a significant decrease in agitation scores in the physostigmine arm compared to the lorazepam arm after the initial bolus (89% vs 30%, p  = 0.02), but no difference at the 4th hour of infusion ( p  > 0.99). There were no seizures, bradycardia, bronchorrhea, bronchospasm, intubation, or cardiac dysrhythmias. Conclusion: Physostigmine was superior to lorazepam in controlling antimuscarinic delirium and agitation after bolus dosing, and control of delirium after a 4-h infusion. There were no serious adverse events in either treatment arm. Physostigmine bolus and infusion should be considered in adolescent patients with significant delirium and agitation from antimuscarinic agents